Modeling of the effects of the electrical dynamics on the electromechanical response of a DEAP circular actuator with a mass–spring load. (21st August 2015) - Rizzello, G; Hodgins, M; Naso, D; York, A; Seelecke, S
Abstract: This paper presents a modeling approach of an actuator system based on a dielectric electro-active polymer (DEAP) circular membrane mechanically loaded with a mass and a linear spring. The motion is generated by the deformation of the membrane caused by the electrostatic compressive force between two compliant electrodes applied on the surface of the polymer. A mass and a linear spring are used to pre-load the membrane, allowing stroke in the out-of-plane direction. The development of mathematical models which accurately describe the nonlinear coupling between electrical and mechanical dynamics is a fundamental step in order to design model-based, high-precision position control algorithms operating in high-frequency regimes (up to 150 Hz). The knowledge of the nonlinear electrical dynamics of the actuator driving circuit can be exploited during the control system design in order to achieve desirable features, such as higher modeling accuracy for high-frequency actuation, self-sensing or control energy minimization. This work proposes a physical model of the DEAP actuator system which couples both electrical and mechanical dynamics occurring during the actuation process. By means of numerous experiments, it is shown that the model can be used to predict both actuator current and displacement, and therefore to increase the overall displacement prediction accuracy with respect to actuator models which neglect electrical behavior.